Implementation of Financial Literacy Development Strategies in Elementary School Students - Darmansyah, Ady; Susanti, Atika; Kurniawati, Ike; Anggraini, Dwi (EduBase : Journal of Basic Education, 2024)
Purpose: This research aims to describe the implementation of financial literacy development strategies for students at SD Negeri 44 Bengkulu City. Methods: Researchers used a qualitative descriptive research design. Data collection techniques in this research include interviews, observation and documentation. The research subjects consisted of the principal, two teachers, fifteen grade 2 students at SD Negeri 44 Bengkulu City, and a coordinator from Bank Bengkulu. The data analysis techniques used by researchers include (1) data condensation; (2) data presentation; (3) drawing conclusions and verification. Results: The research results show that various strategies have been implemented, such as: (1) integration of financial literacy in the Independent Indonesian Language Curriculum Textbook for Class 2, (2) the presence of an honesty canteen, (3) class cash management, and (4) savings activities through Bengkulu Bank. Conclusion: The strategy for developing financial literacy at SD Negeri 44 Bengkulu City has succeeded in increasing students' financial understanding and skills. The implications of the research illustrate the importance of collaboration between schools, parents and Bank Bengkulu to strengthen strategies and integrate elements of financial literacy into the elementary school curriculum.